2004
DOI: 10.1161/01.cir.0000125854.51637.06
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Sex Hormones and Progression of Carotid Atherosclerosis in Elderly Men

Abstract: Background-The burden of atherosclerosis especially afflicts the increasing older segment of the population. Recent evidence has emphasized a protective role of endogenous sex hormones in the development of atherosclerosis in aging men. Methods and Results-We studied the association between endogenous sex hormones and progression of atherosclerosis in 195 independently living elderly men. Participants underwent measurements of carotid intima-media thickness (IMT) at baseline in 1996 and again in 2000. At basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
178
5
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(195 citation statements)
references
References 46 publications
7
178
5
5
Order By: Relevance
“…Carotid artery intima-media thickness, a common marker of clinical and subclinical atherosclerosis, has been shown to be correlated inversely with testosterone levels. [65][66][67] Demirbag et al 68 reported a similar finding by examining the intima thickness of the thoracic aorta in older men. Similarly, in the Rotterdam Study population, Hak et al 69 demonstrated that both bioavailable and total testosterone levels were negatively associated with calcified deposits in the abdominal aorta in men older than 55 years of age.…”
Section: Association Of Low Testosterone With Surrogate Markers Of Atmentioning
confidence: 65%
“…Carotid artery intima-media thickness, a common marker of clinical and subclinical atherosclerosis, has been shown to be correlated inversely with testosterone levels. [65][66][67] Demirbag et al 68 reported a similar finding by examining the intima thickness of the thoracic aorta in older men. Similarly, in the Rotterdam Study population, Hak et al 69 demonstrated that both bioavailable and total testosterone levels were negatively associated with calcified deposits in the abdominal aorta in men older than 55 years of age.…”
Section: Association Of Low Testosterone With Surrogate Markers Of Atmentioning
confidence: 65%
“…Moreover, hypogonadism is associated with increased insulin resistance and progression of atherosclerosis [2,29]. Because men with type 2 diabetes have relative hypogonadism, supplementation with androgen might reduce both insulin resistance and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Data on reproducibility on the intima-media thickness measurements come from several studies that we performed at the Julius Centre, using the same training, certification and reading procedures as the present study with the same readers. These studies showed an intraclass correlation coefficient ranging from 0.84 to 0.92 for repeated common CIMT measurement in single-and multicentre studies [22][23][24].…”
Section: Assessment Of Carotid Atherosclerosismentioning
confidence: 96%